Homoallylic amines as efficient chiral inducing frameworks in the conjugate addition of amides to α, β-unsaturated esters. An entry to enantio-enriched diversely substituted amines. Issue 14 (30th January 2020) - Rogier, Johann; Anani, Lilia; Coelho, Aurélien; Massicot, Fabien; Machado-Rodrigues, Carine; Behr, Jean-Bernard; Vasse, Jean-Luc
Abstract : The diastereoselective conjugate addition of chiral secondary lithium homoallylamides to α, β-unsaturated esters, providing tertiary amines bearing two chains integrating a stereogenic center adjacent to the nitrogen atom, is reported. Abstract : The diastereoselective conjugate addition of secondary homoallylamines, obtained in the enantioenriched form via allylmetallation of imines, to α, β-unsaturated esters is reported. This method allows access to valuable building blocks as well as heterocyclic skeletons, providing tertiary amines bearing two chains integrating a stereogenic center adjacent to the nitrogen atom.